Deconstruction roles in the construction and demolition waste management in Portugal: from design to site management - Couto, J. Pedro (2011)
In the last few years, the impact of construction industry on the environment has been increasingly recognized and has become a key challenge for the sector. Construction sites activities in urban areas may cause damage to the environment, interfering in the day life of local residents, that frequently claim against dust, mud, noise, traffic delay, space intrusion, materials or waste deposition in public space, etc.. In a time where it can be seen quality improvements in construction process techniques, in materials innovation and in safety and healthy conditions, it is also necessary to take care of the environment and other sustainability related issues. The number of new constructions in Portugal had a significant decrease on the last years. This is due to the fact that housing needs are already completely fulfilled - one dwelling per each two inhabitants. This is the result of a construction boom that took place during the 80s and 90s of the past century. But many of these buildings were made without a sustainable cost/benefit ratio and without reuse / recycling strategies, due to initial budget limitations and lack of knowledge. In recent years, the implementation of Energetic Certification by Decree-Law 78/2006, from 4th of April, following the 2002/91/EC directive as well as new regulation on Buildings’ construction waste management, Decree-Law 46/2008, from 12th of March, following the 2006/12/EC directive, conducted to relevant changes, especially regarding envelope walls, but also with repercussions on the interior layouts. There is a need of refurbishment that in some cases reflects both in the quality improvement of the construction, but also in the increase of the internal areas. The internal minimum areas have increased significantly in the last 50 years, and almost doubled, what made many buildings obsolete and not capable of fulfilling the contemporary needs of the households. Maybe this is the reason why the majority (66,9%) of the refurbishment building works taking place in Portugal in the last years correspond to extensions. Refurbishment works and rehabilitation without extensions correspond to 33,1% (INE, 2010).